The Value of Small Live Music Venues: Alternative Forms of Capital and Niche Spaces of Cultural Production. (December 2021) - Whiting, Sam
Small live music venues rely on complex systems of cultural and social capital to bring revenue into each venue space. Although these intangible forms of value are quickly exchanged for economic capital over the bar or through the ticket vendor, their initial state conveys the intrinsic value of small venues as spaces of sociality and cultural production. Throughout this article I demonstrate the intrinsic value of small venues through an analysis of how alternative forms of capital – social, cultural, and symbolic (Bourdieu, 1984, 1986, 1997, 2002) – are generated and mobilised by individuals working in small venues, and the venue spaces themselves. This utilisation of Bourdieu and his theoretical apparatus forms the conceptual framework of this article, as I assert that much of the 'work' that small venues 'do' is intangible, and thus difficult to measure in quantitative terms. However, Bourdieu's alternative forms of capital allow us to qualitatively assess the intrinsic value of small live music venues, demonstrating the significance of this value whilst also prompting a discussion of the nature of intrinsic and instrumental value. This article is both a review of the literature connecting Bourdieu to the study of small live music venues and an analysis of how theories of value and Bourdieusian capital(s) play out in niche spaces of cultural production such as small live music venues.